Home > Conversions (Length) > Conversion tables from/to em > em to ftm Conversion Cheat Sheet (Interactive)
 From: Step: Decimals: 0 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 You could also enter the values to convert and print directly on the table
 [Formula: ftm = em x 2.31479658792651E-03]   [Printer friendly]  [Fathoms to Ems]
em   ftm
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
em   ftm
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
em   ftm
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
em   ftm
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##
=  ##

# Ems to Fathoms Conversion Table

 em  =  2.31479658792651E-03 ftm

# How to convert from Ems to Fathoms

Since 1 em is equal to 2.31479658792651E-03 fathoms, we could say that n ems are equal to 2.31479658792651E-03 times n fathoms. In other words, we could use the following formula:

fathoms = ems x 2.31479658792651E-03

For example, let's say that we want to convert 2 ems to fathoms. Then, we just replace ems in the abovementioned formula with 2:

fathoms = 2 x 2.31479658792651E-03

That is, 2 ems are equal to 0.00462959317585 fathoms.